(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2017)
For the ninetieth anniversary of the birth of Pio La Torre, the Review proposes in this section the minority report dated 4 February 1976. The report was drawn up by the deputy La Torre, together with the judge Terranova and it was endorsed by deputies Benedetti, Malagugini and by senators Adamoli, Chiaromonte, Lugnano e Maffioletti by the end of the legislature. The Review publishes the report fully, excluding the annexes. The document highlights limits, inconsistencies and reticence present within the majority report of the parliamentary Antimafia Commission, chaired by senator Carraro. The minority report focused in particular on the topic omitted by the majority: the interchange between mafia and politics. Furthemore, the report contains the legislative proposals that have become law in 1982 (Law Rognoni-La Torre), just after the murders of Pio La Torre and Carlo Alberto dalla Chiesa. Keywords: Pio La Torre; Sicily, mafia and politics, 1976, parliamentary Antimafia Commission